Surface immobilization of viruses and nanoparticles elucidates early events in Clathrin-Mediated endocytosis - Fratini, Marta; Wiegand, Tina; Funaya, Charlotta; Shah, Pranav; Spatz, Joachim P.; Cavalcanti-Adam, Elisabetta A.; Boulant, Steeve (ACS infectious diseases, 2018)
Surface Immobilization of Viruses and Nanoparticles Elucidates Early Events in Clathrin-Mediated Endocytosis
Gesehen am 27.03.2019